Analisis Pengaruh Konflik Rempang Galang terhadap Destinasi Wisata - Suwandi, Amillia; Kuncoro, Agus (Journal of Tourism Sciences, Technology and Industry, 2023)
The case of the Rempang community occurred due to the lack of legal protection for their land which was then labeled as squatters. Due to misunderstandings between local communities and the government, this creates quite serious conflicts due to territorial struggles. The RempangGalang conflict caused a decrease in the number of visitors to tourist areas on the island. The decline in the number of visitors has caused the local economy to decline. In fact, the chaos that occurred between the government and the Rempang community made visitors afraid to go on tours to tourist areas around Rempang-Galang.